2013
DOI: 10.1007/s12182-013-0295-0
|View full text |Cite
|
Sign up to set email alerts
|

Development characteristics of the fault system and its control on basin structure, Bodong Sag, East China

Abstract: The Bodong Sag, located in the Bohai Sea, offshore China, is one of the most petroliferous basins in China. Based on three dimensional seismic reflection data and time slice data, we analyze the fault system of the Bodong area in detail, establish the fault structure pattern of different types and summarize the distribution of the fault system. It is concluded that the development characteristics of the a brush structure with NNE strike-slip faults as its principal faults, NE-trending extensional faults as sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This kind of the “flower‐structure” with a dip‐slip component is widely observed in the BBB (Hu, Jiang, Fu, Li, & Chen, 2016; Wu et al, 2013; Xu et al, 2015) and sometimes noted as the “flower‐like structure” (Liu, Dong, & Wang, 2010; Zhan et al, 2012). The formation mechanism was studied and illustrated as a result of wrench activity imposed on pre‐existing extension faults (Wu et al, 2013; Yixin et al, 2018), which has also been confirmed by physical modelling experiments (Richard & Krantz, 1991; Hu et al, 2019).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This kind of the “flower‐structure” with a dip‐slip component is widely observed in the BBB (Hu, Jiang, Fu, Li, & Chen, 2016; Wu et al, 2013; Xu et al, 2015) and sometimes noted as the “flower‐like structure” (Liu, Dong, & Wang, 2010; Zhan et al, 2012). The formation mechanism was studied and illustrated as a result of wrench activity imposed on pre‐existing extension faults (Wu et al, 2013; Yixin et al, 2018), which has also been confirmed by physical modelling experiments (Richard & Krantz, 1991; Hu et al, 2019).…”
Section: Resultsmentioning
confidence: 89%
“…The dashed grey frames give the locations of the seismic slices discussed in Figures 5 and 7 [Colour figure can be viewed at wileyonlinelibrary.com] strata thickness of the hanging and the footwall varies a lot. This kind of the "flower-structure" with a dip-slip component is widely observed in the BBB (Hu, Jiang, Fu, Li, & Chen, 2016;Wu et al, 2013; and sometimes noted as the "flower-like structure" (Liu, Dong, & Wang, 2010;Zhan et al, 2012). The formation mechanism was studied and illustrated as a result of wrench activity imposed on pre-existing extension faults (Wu et al, 2013;Yixin et al, 2018), which has also been confirmed by physical modelling experiments (Richard & Krantz, 1991;Hu et al, 2019).…”
Section: Faults In the North Of The Shaleitian Upliftmentioning
confidence: 91%
“…It is well accepted that the sinistral motion of the TLZF is triggered by the NNW‐directed subduction of the Pacific to the Eurasian plates in the Early Paleogene, and its dextral motion is attributed to the sudden kinematic adjustment of the Pacific Plate from NNW to WNW at about 43 Ma, corresponding to the bend point of the Hawaiian–Emperor chain (e.g., Huang et al, ; Wu et al, ; Zhou, ). However, this viewpoint is not only too general to match what we found in the Weibei, Qingdong, and Dongying sags but also has intrinsic weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strike‐slip transition time of the TLFZ is still controversial. Some scholars held the opinion that this transition occurred between the Mesozoic and Cenozoic (e.g., Cai, Luo, & Yao, ; Cheng et al, ; Wan & Zhu, ; Zhang & Qi, ), but more and more authors considered that it happened in Early Paleogene, for example, in the depositional stage of (1) the second member of the Kongdian Formation (designated as E k 2 ; e.g., Sun et al, ; Zhou, ), (2) E k (Chen, ; Chen, ; Wang, ), (3) E k to the fourth member of the Shahejie Formation (E k ‐E s 4 ; e.g., Cao, ; Guo, ; Gao, ; Huang, Wang, Wu & Wang, ; Huang, Liu, Zhou & Wang, ; Jia et al, ; Wu et al, ; Zheng et al, ; Zhang, Wang, Ding, & Zhong, ; Zhao & Li, ), (4) E k to the lower sub‐member of E s 4 (E k ‐E k 4 L ; e.g., Jia et al, ; Jia et al, ; Wang et al, ; Wei et al, ; Wu et al, ; Yang, ; Zhang, ; Zheng et al, ), or (5) E s 4 (e.g., Chen, ) and in geological time (1) in the Palaeocene (e.g., Shi, ), (2) from the Palaeocene to the Early Eocene (e.g., Han et al, ; Hsiao et al, ; Huang, Yu, Zhang, Fu, Yuan, & Fan, ; Li et al, ; Teng, Zou, & Hao, ; Xia, Liu, & Chen, ; Xu et al, ; Zhang et al, ; Zhang, ; Zhang et al, ; Zhang, Xue, Wu, Nie, & Hu, ; Zheng, ; Zhou, ), or (3) in the Early Eocene (e.g., Gao, ; Wang, Zhang, & Li, ). Besides, they did not explain how exactly the TLFZ turned into dextral motion from sinistral motion during the above transition stage as well (e.g., Gao, ; Huang et al, ; Jia et al, ; Wu et al, ; Zhao & Li, ; Zheng et al, ; Zhou, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation